Intracellular KRAS-specific antibody enhances the anti-tumor efficacy of gemcitabine in pancreatic cancer by inducing endosomal escape - Lee, Ji Eun; Kang, Yeo Wool; Jung, Kyung Hee; Son, Mi Kwon; Shin, Seung Min; Kim, Ji Sun; Kim, Soo Jung; Fang, Zhenghuan; Yan, Hong Hua; Park, Jung Hee; Yoon, Young Chan; Han, Boreum; et al. (Cancer Letters, 2021)
KRAS mutation is associated with the progression and growth of pancreatic cancer and contributes to chemo-resistance, which poses a significant clinical challenge in pancreatic cancer. Here, we developed a RT22-ep59 antibody (Ab) that directly targets the intracellularly activated GTP-bound form of oncogenic KRAS mutants after it is internalized into cytosol by endocytosis through tumor-associated receptor of extracellular epithelial cell adhesion molecule (EpCAM) and investigated its synergistic anticancer effects in the presence of gemcitabine in pancreatic cancer. We first observed that RT22-ep59 specifically recognized tumor-associated EpCAM and reached the cytosol by endosomal escape. In addition, the anticancer effect of RT22-ep59 was observed in the high-EpCAM-expressing pancreatic cancer cells and gemcitabine-resistant pancreatic cancer cells, but it had little effect on the low-EpCAM-expressing pancreatic cancer cells. Additionally, co-treatment with RT22-ep59 and gemcitabine synergistically inhibited cell viability, migration, and invasion in 3D-cultures and exhibited synergistic anticancer activity by inhibiting the RAF/ERK or PI3K/AKT pathways in cells with high-EpCAM expression. In an orthotopic mouse model, combined administration of RT22-ep59 and gemcitabine significantly inhibited tumor growth. Furthermore, the co-treatment suppressed cancer metastasis by blocking EMT signaling in vitro and in vivo. Our results demonstrated that RT22-ep59 synergistically increased the antitumor activity of gemcitabine by inhibiting RAS signaling by specifically targeting KRAS. This indicates that co-treatment with RT22-ep59 and gemcitabine might be considered a potential therapeutic strategy for pancreatic cancer patients harboring KRAS mutation.
Keywords: Animals; Antimetabolites, Antineoplastic; Antineoplastic Agents, Immunological; Antineoplastic Combined Chemotherapy Protocols; Cell Line, Tumor; Cell Movement; Cell Proliferation; Deoxycytidine; Drug Resistance, Neoplasm; Drug Synergism; Endocytosis; Endosomes; Epithelial Cell Adhesion Molecule; Epithelial-Mesenchymal Transition; Humans; Male; Mice, Inbred BALB C; Mice, Nude; Mutation; Neoplasm Invasiveness; Pancreatic Neoplasms; Proto-Oncogene Proteins p21(ras); Tumor Burden; Xenograft Model Antitumor Assays; Endosomal escape; Gemcitabine; KRAS target antibody; Pancreatic cancer